Charities Can Increase the Effectiveness of Donation Appeals by Using a Morally Congruent Positive Emotion - Goenka, Shreyans; van Osselaer, Stijn M J (Journal of Consumer Research, 2019)
Abstract Prosocial organizations have different moral objectives. Some seek to promote welfare (e.g., Red Cross), but others seek to promote justice and equality (e.g., ACLU). Additionally, these organizations can induce different positive emotions to motivate donations. If organizations are seeking to promote different moral objectives using positive emotions, which positive emotion will be the most effective for their respective campaigns? We demonstrate how the congruency between the moral domain of an emotion and the moral objective of an organization plays a role in influencing prosocial behaviors. Charities that seek to increase care in society (e.g., disaster-relief charities) should utilize compassion in their promotion campaigns, but charities that seek to promote fairness and equality in society (e.g., human rights charities) should utilize gratitude in their promotion campaigns. One field study (N = 2,112) and four experiments (N = 2,100) demonstrate that utilizing a positive emotion congruent with the charity’s moral objective increases monetary donations and preferences. The preferences are driven by the moral concerns made salient by the respective emotions. Further, the preferences attenuate when exchange norms are made salient. Altogether, these results underscore the importance of considering moral congruence in consumption contexts.